A framework for managing human resources in secondary schools for improved educational perfomance - Ralenkoane, Makhube M. (University of the Free State, 2013)
English: The concept of human resource management (HRM) comes into education as a result of a series of reforms meant to improve the quality of education for all, worldwide. These reforms have encouraged many countries to rigorously engage in initiatives that are meant to improve the quality of their educational governance and management structures. More emphasis was put on managing the crucial human resource during the teaching and learning process, which is the teacher. Evidence from literature has shown that a collective teacher-quality has a positive impact on learners' performance, however, the management of these crucial resources has been an unintelligible hollow in the educational management which in this study is the management of human resources in a high-performance public secondary school in Lesotho. My ultimate aim has been to develop and recommend a framework for use in the effective management of these resources in secondary schools that are unable to procure sufficient educational resources. I have adopted critical theory and the participatory inquiry research paradigms in my methodology, in order to emphasise inclusiveness, respect for human dignity and empowerment for the research participants. I further have used a combination of the ethnographic research methods that include unstructured interviews and observation techniques and analysed the data through the critical discourse analysis method. From the findings I have identified two. sets of respondents whose inputs I value equally as the managed (teachers who do not hold managerial positions) and the managers (teachers who occupy managerial positions). The information I obtained from these respondents has revealed two distinct sources of meaning that motivate at least eleven different interactional spaces within the case study school's HRM structures and processes. These are the sources of meaning for the school and for teachers respectively. It is within these social interaction intercourses that the HRM strategies at the case study secondary school are used. From the analysis of the impact that they have on the specific interactional spaces at this school, I was able to develop a framework for managing human resources at the public secondary schools that would be applicable to other schools within similar educational settings.

Afrikaans: Die begrip menslike hulpbronbestuur (MHB) het die terrein van die opvoedkunde betree as gevolg van 'n reeks hervormings bedoel om die gehalte van onderwys vir almal, wêreldwyd, verbeter. Hierdie hervormings het talle lande aangespoor om doelgerig betrokke te raak by inisiatiewe wat ten doel het om die gehalte van hulle opvoedkundige gesagsverhouding en bestuurstrukture te verbeter. Meer klem is geplaas op die bestuur van kritieke menslike hulpbronne tydens die leer en onderrigproses, wat die onderwyser is. Bewys uit die literatuur het aangetoon dat 'n kollektiewe gehalte-onderwyser 'n positiewe impak op leerders se prestasie het. Die bestuur van hierdie deurslaggewende hulpbronne was egter tot op datum 'n tot nog toe 'n onverstaanbare gaping in die onderwysbestuur, wat in hierdie studie die bestuur van menslike hulpbronne in 'n hoëprestasie openbare sekondêre skool in Lesotho is. My uiteindelike oogmerk was om 'n raamwerk te ontwikkel en aan te beveel vir gebruik in die doeltreffende bestuur van hierdie hulpbronne by sekondêre skole wat nie in staat is om toereikende onderwyshulpbronne aan te skaf nie. Ek het kritiese teorie en die deelnemende ondersoekende navorsing paradigmas in my metodologie aangepas ten einde inklusiwiteit, respek vir menswaardigheid en bemagtiging vir die deelnemers aan die navorsing te beklemtoon. Vanuit die bevindings het ek twee stelle respondente geïdentifiseer aan wie se insette ek net soveel waarde heg as die bestuurder (onderwysers wat nie in bestuursposies is nie) en die bestuurders (onderwysers wat bestuursposisies beklee). Die inligting wat ek van hierdie respondente bekom het, het twee kenmerkende bronne van stelle betekenisse wat ten minste elf verskillende interaksionele ruimtes binne die gevallestudieskool se MHB-strukture en prosesse. Hierdie is die bronne van betekenis vir onderskeidelik die skool en vir onderwysers. Dit is binne hierdie sosiale interaksionele gemeenskappe wat die MHB-strategieë by die gevallestudie sekondêre skool gebruik is. Vanuit die ontleding van die impak wat hulle op die spesifieke interaksionele ruimtes by hierdie skool gehad het, was ek in staat om 'n raamwerk te ontwikkel vir die bestuur van menslike hulpbronne by die openbare sekondêre skole wat toepaslik sal wees vir ander skole binne soortgelyke opvoedkundige omgewings.
Keywords: Critical discourse analysis; Critical theory; Education quality; Educational governance; Empowerment; Human resource; Human resource management; Human resource structures; Inclusiveness; Learner performance; Participatory inquiry; Performance management; Professional development; Teacher-quality; Total quality management in education -- Lesotho; Employee empowerment -- Lesotho; Education -- Lesotho -- Personnel management; Teacher effectiveness -- Lesotho; Academic achievement -- Lesotho; Thesis (Ph.D. (Educational Management and Comparative Education))--University of the Free State, 2013